Recurrent syncope in patients with a pacemaker and bradyarrhythmia. (25th November 2020) - Lee, C.J.Y; Davidsen, J.M; Skals, R; Torp-Pedersen, C; Soegaard, P
Abstract: Objectives: To investigate the risk of recurrent syncope and all-cause mortality after implantation of a pacemaker in patients with bradyarrhythmia. Background: A pacemaker is generally recommended when syncope is caused by bradyarrhythmias to prevent a new syncope. However, the occurrence and risk of recurrent syncope in patients with bradyarrhythmia after pacemakerimplantation are still unknown. Methods: Patients with a prior syncope and an implantation of pacemaker were identified. Cumulative incidences of 5-years were estimated for the outcomes stratified into groups according to the type of bradyarrhythmia; and type of pacemaker. The risk of recurrent syncope and all-cause mortality were estimated using adjusted cox proportional hazard regressions. Results: We identified 8, 663 patients with a prior syncope and pacemaker implantation (median age of 78, 1 years (SD 69, 1–84, 8) and 55, 1% males). The 5-year cumulative incidence of recurrent syncope was 19, 3% (95% confidence intervals (CI) 18, 4–20, 2). Factors associated with a significant increased risk of recurrent syncope were male sex, age 80 years and above, alcohol related disease, bleeding, chronic obstructive pulmonary disease, chronic kidney disease, stroke, and malignancy. Atrial fibrillation was associated with a significantly decreased risk of recurrent syncope. Patients with an advanced AV conduction abnormality had a lower associated risk of syncope compared to patients with sinus node dysfunction (HR 0, 85, 95% CI 0, 76–0, 94, p=0, 003). Conclusions: One fifth of the cohort had a recurrence syncope after five years. Besides older age and male sex, several comorbidities were found to be associated with a higher risk of recurrence of syncope. Clinicians need to be attentive that a large proportion of patients with bradyarrhythmia suffer from syncope even when treated with a pacemaker. Funding Acknowledgement: Type of funding source: None